Liquidez en los mercados accionarios colombianos. Cuánto hemos avanzado en los últimos 10 años? (2010)
How to measure the liquidity of Colombian stocks and its recent evolution. In the context of market microstructure literature, we define and estimate a measure of liquidity for Colombian stocks and provide evidence of the large improvement of the Colombian stock market in terms of the overall market liquidity from 2001 to 2007. Moreover, the merger of the former three stock exchanges (Bogotá, Medellín and Cali) into the Bolsa de Valores de Colombia in July 2001 can be associated, in an econometric model, to a significant improvement in liquidity for most of the individual stocks.